2011
DOI: 10.1111/j.1540-5982.2011.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Us’ and ‘Them’: the origin of identity, and its economic implications

Abstract: We investigate the origins of identity and the innate proclivity to draw a distinction between 'insiders' and 'outsiders'. We propose an evolutionary explanation: we argue that identity arises because it facilitates survival. In an evolutionary setting we endogenize preferences and demonstrate that the evolutionarily stable preferences fashioned by natural selection would distinguish between insiders and outsiders. We then work out the implications of such preferences in two contemporary scenarios, one entaili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…Evolutionary stability of other-regarding preferences has generated considerable interest inside economics. 8 An important paper that is closest in spirit to our research question and considers competition between groups is Eaton et al (2011) who also aim at an explanation of in-group favoritism. They consider a framework which combines two distinct action choices: production e¤ort and appropriation e¤ort in a model of con ‡ict.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evolutionary stability of other-regarding preferences has generated considerable interest inside economics. 8 An important paper that is closest in spirit to our research question and considers competition between groups is Eaton et al (2011) who also aim at an explanation of in-group favoritism. They consider a framework which combines two distinct action choices: production e¤ort and appropriation e¤ort in a model of con ‡ict.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of con ‡ict, Eaton and Eswaran (2003) and Leininger (2009) studied evolutionary stability of preferences in contests between individuals and also found evolutionary foundations for spiteful preferences. 10 In a late stage of this work we became aware of a paper by Eaton et al (2011), who also consider at the framework of in-group favoritism with out-group competitors. Their analysis is based on observability of types -hence their results are essentially based on a combination of known results about evolutionary stability of altruism (as in Bester and Güth 1998) and spite (Eaton and Eswaran 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals tend to be more cooperative with individuals with whom they share a common social identity (in-group) than with individuals who belong to different social groups (out-group) (Solow and Kirkwood, 2002). Often referred to as ingroup bias, this behavioral pattern seems to be deeply rooted in human nature (Eaton et al, 2011) and can be found in many different cooperative settings (cf. McLeish and Oxoby, 2007;Chen and Li, 2009;Charness et al, 2007;Chen and Chen, 2011;Goette et al, 2006).…”
Section: Introductionmentioning
confidence: 99%